Formation Damage Removal Through Acidizing of an Oil Well After Drilling and Completion - Sarhad A. Farkha; Farhad A. Khoshnaw; Pshtiwan T. Jaf (European Scientific Journal, ESJ, 2017)
This paper discusses a real case study on how formation damage can be removed after finishing all operations in drilling and completing a well that is used vertically for producing commercial hydrocarbons using Over Balanced Drilling (OBD) techniques. Formation damage happens in every drilled well during field operations. It is an undesirable and complicated situation usually caused by solids invasion, fines movements, organic precipitation and deposition, and collapse and swelling formations (clay formations). The production performance of drilled well is significantly affected by the scale of damage in the invaded formation of the pay zone. The process of finding ways to solve this problem and the mechanism of preventing formation damages are the most important efforts faced by oil and gas industries. Formation damage is even a difficult problem to diagnose, but there are still some steps used for indicating it. For instance, this includes; well testing, well history reports, and well logging analysis. However, these techniques can only carry out diagnosis and an overall measure of the damage. Also, the results can apply suitable mechanisms for minimizing the risks and reducing the causes. After drilling and completing a well in Field A in Kurdistan region-north of Iraq, acid job is performed for the well considering the other wells potential and productivity. This is because the level was not enough for oil to be delivered to degassing station with the request pressure as shown in the appendix figures of pressure versus depth and tables of surface well testing results. Acidizing is a mean of production optimization for naturally flowing wells, whereby a designed acid volume is pumped to remove the damaged interval. Hence, it aims to increase the flow of oil to the surface. The type of acid used was Hydrochloric acid (HCL) with a concentration of 15%. In choosing the acid concentration, historical stimulation operation and lab tests were considered as the field is been developed a long-time ago. Here, enough programming data were made available for proposing operation of which one of them is acidizing. In the mentioned Field A, wells with high pressure drop between the well that was shut in and flowing pressure are required to be stimulated through acidizing. In this case, the pressure difference was about 300 psig before performing the job. Thus, the aim of this job was to obtain the optimum pressure difference between Bottom hole flowing pressure ???????????? and Sand face well pressure ???????????? which yields to the maximum oil production rate. The objectives of the job were achieved after obtaining a high flow rate of 8000 bbl/day at the surface and from the slickline data measurement. This recorded too much lesser draw down pressure of 11 psig between ???????????? & ????????????.